Exploring barriers to the effective use of computer-based simulation in pharmacy education: a mixed-methods case study - Gharib, Ahmed M.; Peterson, Gregory M.; Bindoff, Ivan K.; Salahudeen, Mohammed S. (Frontiers in Medicine, 2024)
Background: At the University of Tasmania (UTAS), pharmacy education traditionally relies on placements to provide students with hands-on experience. However, these placements have become increasingly limited due to logistical challenges and growing student numbers.Computer-based simulation (CBS) has the potential to offer a scalable, effective alternative to enhance learning and critical thinking. However, integrating CBS in pharmacy education faces several barriers that must be addressed for successful implementation.Objective: To gain insight into pharmacy educators' and students' views regarding the barriers, and potential solutions, to integrating CBS in pharmacy practice education.Methods: This mixed-methods case study involved semi-structured interviews with pharmacy educators and quantitative surveys with pharmacy students. The data underwent thematic coding for interview transcripts and statistical analysis for survey responses. The findings were integrated by examining convergence, complementarity, and discrepancy, revealing insights into how pharmacy students and educators perceive implementation barriers and improvement strategies for CBS.Results: Ten interviews were conducted, and 75 survey responses were collected, with a 62.5% response rate. Key barriers to CBS integration included educators' heavy workload, scepticism about CBS's educational value, and general integration challenges. Students, however, showed high acceptance of CBS, with 70.7% agreeing that CBS could assess their knowledge, 69.3% emphasizing its role in developing problem-solving skills, and 80% viewing CBS as a complement to classroom study. Proposed solutions for enhancing CBS uptake included additional institutional support by appointing dedicated simulation technicians, leveraging champions to advocate for CBS, and aligning CBS with educational objectives.Conclusions: A significant gap between students' readiness and educators' hesitancy to use CBS in pharmacy education was identified. While students are eager to adopt new technologies, educators expressed reservations, primarily due to workload concerns and uncertainties about the efficacy of CBS. The feedback from educators suggests that institutions may see improved uptake by employing dedicated support personnel and initiating targeted training programs. Future research should focus on exploring barriers and facilitators, using larger and more diverse samples, and gaining deeper insights into decisionmakers' perspectives to enhance the integration and efficacy of CBS in pharmacy education.